Understanding Cyber Warfare : politics, policy and strategy - Whyte, Christopher 1988-; Mazanec, Brian M. (London and New York: Routledge, Taylor & Francis, 2023)
"This textbook offers an accessible introduction to the historical, technical, and strategic context of global cyber conflict. The 2nd edition has been revised and updated throughout, with three new chapters. Cyber warfare involves issues of doctrine, strategy, policy, international relations and operational practice associated with computer network attack, computer network exploitation, and computer network defense. However, it is conducted within complex sociopolitical settings alongside related forms of digital contestation. This book provides students with a comprehensive perspective on the technical, strategic and policy issues associated with cyber conflict, as well as an introduction to key state and non-state actors. Specifically, the book provides a comprehensive overview of several key issue areas: - The historical context of the emergence and evolution of cyber warfare, including the basic characteristics and methods of computer network attack, exploitation, and defense; - An interdisciplinary set of theoretical perspectives on conflict in the digital age from the point of view of the fields of international relations (IR), security studies, psychology and Science, Technology and Society (STS) studies; - Current national perspectives, policies, doctrines, and strategies relevant to cyber warfare; - An examination of key challenges in international law, norm development and deterrence; and - The role of emerging information technologies like artificial intelligence and quantum computing in shaping the dynamics of global cyber conflict. This textbook will be essential reading for students of cybersecurity/cyber conflict and information warfare, and highly recommended for students of intelligence studies, security and strategic studies, defense policy, and International Relations in general"
Keywords: Cyberspace Operations (Military Science)